2017
DOI: 10.1002/ijc.31225
|View full text |Cite
|
Sign up to set email alerts
|

Telomerase reverse transcriptase mutations are independent predictor of disease‐free survival in Middle Eastern papillary thyroid cancer

Abstract: Papillary thyroid carcinoma (PTC) is the most common type of thyroid cancer. Tumor recurrence occurs in ∼20% of PTCs and some reach advanced stages. Promoter mutation in the telomerase reverse transcriptase (TERT) gene is identified to be a prognostic marker in PTC. However, the contribution of TERT promoter mutation to cancer progression in PTC patients is still not fully understood. In this study, we investigated the incidence of TERT promoter mutations and TERT protein expression and their association with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
52
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(63 citation statements)
references
References 59 publications
10
52
0
Order By: Relevance
“…Among 51 studies of overall DTC, 39 [11,[14][15][16][17][18][19][20], 26 [11, 14-17, 19, 20, 26-28, 32, 35, 36, 38-41, 44, 45, 47, 48, 51, 53, 54, 56, 57], 19 [11, 14-16, 19, 20, 27, 32, 35, 36, 44, 45, 47, 48, 53, 54, 56-58], 20 [17, 19, 20, 27, 30, 31, 34-37, 40, 42, 46-48, 51, 54, 55, 59, 60], 11 [16,17,20,28,31,37,44,50,55,57,60] [16-18, 20, 27, 28, 30, 31, 33, 35-38, 42, 43, 46, 56, 58, 60, 62, 64-67], and 14 [14,16,18,20,26,28,29,39,42,46,47,60,66,68] studies were analyzed for the associations between TERT promoter mutation and gender, mean age, mean tumor size, multifocality, vascular invasion, extrathyroidal extension, LNM, distant metastasis, advanced TNM stage, persistence/recurrence, and diseasespecific mortality, respectively. Among 41 studies of PTC, 32 [11, 14-19, 27-31, 33, 35-40, 42, 43, 45-47, 49-56], 19 [11, 14-17, 19, 27, 28, 35, 36, 38-40, 45 [17, 18, 27, 28, 30, 31, 33, 35-37, 39, 42, 43, 46, 56, 58, 62, 64, 66], and 10 [14,16,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among 51 studies of overall DTC, 39 [11,[14][15][16][17][18][19][20], 26 [11, 14-17, 19, 20, 26-28, 32, 35, 36, 38-41, 44, 45, 47, 48, 51, 53, 54, 56, 57], 19 [11, 14-16, 19, 20, 27, 32, 35, 36, 44, 45, 47, 48, 53, 54, 56-58], 20 [17, 19, 20, 27, 30, 31, 34-37, 40, 42, 46-48, 51, 54, 55, 59, 60], 11 [16,17,20,28,31,37,44,50,55,57,60] [16-18, 20, 27, 28, 30, 31, 33, 35-38, 42, 43, 46, 56, 58, 60, 62, 64-67], and 14 [14,16,18,20,26,28,29,39,42,46,47,60,66,68] studies were analyzed for the associations between TERT promoter mutation and gender, mean age, mean tumor size, multifocality, vascular invasion, extrathyroidal extension, LNM, distant metastasis, advanced TNM stage, persistence/recurrence, and diseasespecific mortality, respectively. Among 41 studies of PTC, 32 [11, 14-19, 27-31, 33, 35-40, 42, 43, 45-47, 49-56], 19 [11, 14-17, 19, 27, 28, 35, 36, 38-40, 45 [17, 18, 27, 28, 30, 31, 33, 35-37, 39, 42, 43, 46, 56, 58, 62, 64, 66], and 10 [14,16,…”
Section: Resultsmentioning
confidence: 99%
“…, 47, 51, 53, 54, 56], 14[11, 14-16, 19, 27, 35, 36, 45, 47, 53, 54, 56, 58], 16 [17, 19, 27, 30, 31, 35-37, 40, 42, 46, 47, 51, 54, 55, 59], 7 [16, 17, 28, 31, 37, 50, 55], 23 [14-17, 19, 27, 30, 31, 35-38, 42, 43, 45, 46, 49-52, 54, 58, 61], 32[11, 14-19, 27-31, 33, 35, 37, 38, 40, 43, 45, 46, 49-56, 58, 59, 61, 62], 15[16,17,28,29,31,32,38,39,43,45,46,50,56,62,63], 24[15- 19, 27-31, 35-40, 42, 43, 45, 46, 50, 51, 54, 56],19 …”
mentioning
confidence: 99%
“…Therefore, our study focused on analyzing biopsies of primary PTC and distant metastases to compare the array of somatic mutations. Previously, TERT promoter mutations, in isolation and/or in combination with other driver mutations such as BRAF V600E , have been shown to play an important role in the development of a more aggressive phenotype and the development of metastases (46)(47)(48). The limitation of our exome sequencing approach limits the analyses to exonic mutations, not covering intronic or other regions.…”
Section: Distinct Repertoire Of Genetic Alterations In Primary Ptc Anmentioning
confidence: 99%
“…6 Lymph node metastasis (LNM) is a potential factor that can aggravate the risk of locoregional recurrence and mortality in patients with PTC. [7][8][9][10] Recent studies revealed that several molecular biomarkers, such as BRAF 11,12 TERT, [13][14][15] PIK3CA 16,17 can facilitate LNM to some extent. Despite the in-depth research and progress on PTC studies, comprehensive clinical evaluation and molecular mechanistic exploration remain lacking.…”
Section: Introductionmentioning
confidence: 99%